A case-control epidemiological survey on potential risk factors for celiac disease - Bielik, Matúš; Selvek, Martin; Suchánková, Magda; Shawkatová, Ivana (Central European journal of public health, 2024)
OBJECTIVES: Celiac disease (CD) is a chronic autoimmune disorder caused by a complex interplay between genetic and environmental factors. The main goal of our case-control study was to analyse the association of environmental factors with the odds of CD development in a sample of the Slovak population. METHODS: Data were collected from 1,226 respondents (534 CD patients and 692 controls) by a questionnaire. The impact of analysed parameters on the chance of disease development was assessed by multiple regression analysis and expressed as odds ratios (OR). Values of p < 0.05 were considered statistically significant. RESULTS: In the patient group, celiac disease was significantly more prevalent in women than in men (OR = 1.52, p = 0.010). Respondents with a positive family history of CD showed 2.9-fold higher odds of CD compared to others (p < 0.001), and respondents with coexisting autoimmune diseases had 2.6-fold higher odds of CD (p < 0.001). Subjects who had taken antibiotics at least three times a year during childhood had 1.95-fold higher odds of developing CD compared to those who took them less frequently or not at all (p = 0.022). Conversely, individuals who were breastfed in infancy had lower odds of CD compared to non-breastfed respondents (OR = 0.53, p < 0.001). The mode of delivery (vaginal vs. caesarean section), overcoming severe infections, and the timing of gluten introduction in childhood did not show a statistically significant effect on the odds of developing CD. CONCLUSION: Based on our data, being female, having a positive family history of CD, suffering from another autoimmune disease, and frequent use of antibiotics are factors associated with an increased chance of developing CD. On the other hand, breastfeeding in infancy seems to have a protective effect. Our findings highlight the importance of further research in understanding the complexities of this autoimmune condition and providing a foundation for prevention strategies.
Keywords: senioři; celiac disease; Prevalence; celiakie; mladiství; autoimmune disease; Middle Aged; průzkumy a dotazníky; mužské pohlaví; prevalence; studie případů a kontrol; Adult; Breast Feeding; Celiac Disease; Slovakia; Slovenská republika; environmental factor; ženské pohlaví; Humans; kojení; Surveys and Questionnaires; lidé středního věku; rizikové faktory; risk factor; Case-Control Studies; dospělí; Female; Risk Factors; Aged; Adolescent; epidemiological survey; lidé; Male